ON SOME HUMOROUS ASPECTS OF CONCEPTUAL BLENDING IN POLITICIZED DISCOURSE - Vengalienė, Dovilė (Verbum, 2016)
In this paper, a very dynamic linguistic phenomenon, humour, is analysed on the basis of the Theory of Conceptual Blending developed by Gilles Fauconnier and Mark Turner (2002). It was discovered that in Lithuanian politicized discourse during and after the period of elections (2012, 2016) the majority of political events and personalities were given an evaluative implicit assessment through humour/irony, which can be seen as an emergent result of blending processes. In the paper, the tendency to ridicule politicians and political events on news websites is discussed focusing exceptionally on the processes of blending at the lexical level. The research reveals that the coinage of new lexical units by fusing at least two source words or splinters follows certain patterns. The structural analysis is based on the works of Anita Lehrer, Michael Kelly, Stefan Gries, and Ekaterine Bakaradze. The main claims of the paper are supported by 362 blends collected from the headlines and comments of delfi.lt, lrytas. lt, and blogs, during the period of 2012–2016.
Keywords: cognitive linguistics; conceptual blending; humour; irony; splinters